2014
DOI: 10.1002/adfm.201403124
|View full text |Cite
|
Sign up to set email alerts
|

Facile One‐Step Micropatterning Using Photodegradable Gelatin Hydrogels for Improved Cardiomyocyte Organization and Alignment

Abstract: Hydrogels are often employed as temporary platforms for cell proliferation and tissue organization in vitro. Researchers have incorporated photodegradable moieties into synthetic polymeric hydrogels as a means of achieving spatiotemporal control over material properties. In this study protein-based photodegradable hydrogels composed of methacrylated gelatin (GelMA) and a crosslinker containing o-nitrobenzyl ester groups have been developed. The hydrogels are able to degrade rapidly and specifically in response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 39 publications
1
100
0
Order By: Relevance
“…4C and 4D, also Fig S4). This was previously reported to be a way of quickly and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 18 precisely pre-patterning a flat substrate to present topographical or directional cues to cells 42 .…”
Section: Photo-degradation and Photo-patterning Of The Hydrogelsmentioning
confidence: 85%
“…4C and 4D, also Fig S4). This was previously reported to be a way of quickly and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 18 precisely pre-patterning a flat substrate to present topographical or directional cues to cells 42 .…”
Section: Photo-degradation and Photo-patterning Of The Hydrogelsmentioning
confidence: 85%
“…This hydrogel system was used to culture a cardiomyocyte-cardiac fibroblast co-culture, which exhibited spontaneous beating in vitro. [23] Finally, Eosin Y absorbs well in the visible light spectrum with a peak absorbance at 517 nm. This fluorescent molecule was used as the chromophore of a type-II photoinitiator with triethanolamine as the co-initiator.…”
Section: Ultraviolet Stereolithographymentioning
confidence: 99%
“…2b, the value of G′ for the GelMA/PAM biohybrid hydrogel was higher than that for the GelMA hydrogel and PAM hydrogel over the whole frequency range. Compared with the GelMA hydrogel and PAM hydrogel, the GelMA/PAM biohybrid hydrogel networks were dual crosslinked by both chemical crosslinkage and physical structuring of GelMA and PAM chains, 29 and therefore the GelMA-GelMA crosslinks in the GelMA hydrogel as well as PAM-PAM crosslinks in the PAM hydrogel were replaced with PAM-GelMA crosslinks in the biohybrid hydrogel, which increased the distance between the junctions in the network, leading to high elasticity. The compression tests showed that the GelMA/PAM biohybrid hydrogel had the highest compressive strength of 0.48 MPa at 60% compression strain (Fig.…”
Section: Rheological Analyses Of Hydrogelmentioning
confidence: 99%